Cultivation of Gracilaria (Gracilaria corticata) in the Qeshm Island - Y. Filizadeh (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2000)
The cell walls of certain red algae such as Gracilaria is the sole source of a polysaccharide of major economic importance, agar. Agar is the best known for its use in preparing media for culturing microorganisms. Mariculture of the Gracilaria was conducted in 4 locations of the Qeshm Island during the spring and summer oi 1999. Three culture methods (net, rope, and basket) were tested. The results tested by ANOVA and indicated that the increase in matter up to 45 days after planting was significant (P<0.05) Also the mean yield ropes and nets which were subjected to weekly cleaning was significantly higher than from the uncleaned ropes or nets. The yield net method of cultivation was significantly higher than rope. Experimental results showed that the light intensity, average of temperature, wind and wave action, water and sediment nutrition and some grazers such as turtle had a significant Influence on growth of Gracilaria.